Navigated intramedullary nailing for patients with intertrochanteric hip fractures is cost-effective at high-volume hospitals in mainland China: A markov decision analysis - Tang, Liang; Yi, Xiaoke; Yuan, Ting; Li, Hua; Xu, Cheng (Frontiers in Surgery, 2023)
Objective Previous studies have reported that navigation systems could improve clinical outcomes of intramedullary nailing (IMN) in patients with intertrochanteric fractures. However, information is lacking regarding the relationship between the costs of navigated systems and clinical outcomes. The present research aimed to evaluate the cost-effectiveness of navigated IMN as compared with traditional freehand IMN in patients with intertrochanteric fractures. Methods A Markov decision model with a 5-year time horizon was constructed to investigate the costs, clinical outcomes and incremental cost-effectiveness ratio (ICER) of navigated IMN for a 70-year-old patient with an intertrochanteric fracture in mainland China. The costs (Chinese Yuan [¥]), health utilities (quality-adjusted life-years, QALYs) and transition probabilities were obtained from published studies. The willingness-to-pay threshold for ICER was set at ¥140000/QALY following the Chinese gross domestic product in 2020. Three institutional surgical volumes were used to determine the average navigation-related costs per patient: low volume (100 cases), medium volume (200 cases) and high volume (300 cases). Results Institutes at which 300, 200 and 100 cases of navigated IMN were performed per year showed an ICER of ¥43149/QALY, ¥76132.5/QALY and ¥175083/QALY, respectively. Navigated IMN would achieve cost-effectiveness at institutes with an annual volume of more than 125 cases. Conclusions Our analysis demonstrated that the navigated IMN could be cost-effective in patients with inter-trochanteric fracture as compared to traditional freehand IMN. However, the cost-effectiveness was more likely to be achieved at institutes with a higher surgical volume.